Quantitative Proteomics Reveals Dynamic Interaction of c-Jun N-terminal Kinase (JNK) with RNA Transport Granule Proteins Splicing Factor Proline- and Glutamine-rich (Sfpq) and Non-POU Domain-containing Octamer-binding Protein (Nono) during Neuronal Differentiation - Sury, Matthias D. (Mol Cell Proteomics, 2015)
The c-Jun N-terminal kinase (JNK) is an important mediator of physiological and pathophysiological processes in the central nervous system. Importantly, JNK not only is involved in neuronal cell death, but also plays a significant role in neuronal differentiation and regeneration. For example, nerve growth factor induces JNK-dependent neuronal differentiation in several model systems. The mechanism by which JNK mediates neuronal differentiation is not well understood. Here, we employed a proteomic strategy to better characterize the function of JNK during neuronal differentiation. We used SILAC-based quantitative proteomics to identify proteins that interact with JNK in PC12 cells in a nerve growth factor–dependent manner. Intriguingly, we found that JNK interacted with neuronal transport granule proteins such as Sfpq and Nono upon NGF treatment. We validated the specificity of these interactions by showing that they were disrupted by a specific peptide inhibitor that blocks the interaction of JNK with its substrates. Immunoprecipitation and Western blotting experiments confirmed the interaction of JNK1 with Sfpq/Nono and demonstrated that it was RNA dependent. Confocal microscopy indicated that JNK1 associated with neuronal granule proteins in the cytosol of PC12 cells, primary cortical neurons, and P19 neuronal cells. Finally, siRNA experiments confirmed that Sfpq was necessary for neurite outgrowth in PC12 cells and that it most likely acted in the same pathway as JNK. In summary, our data indicate that the interaction of JNK1 with transport granule proteins in the cytosol of differentiating neurons plays an important role during neuronal development.